Carbonized polymer molecular cluster stable foam system as well as preparation method and application thereof
A carbonized polymer molecular cluster foam system addresses stability and salt resistance issues by using citric acid, taurine, and hexylamine to create a stable foam system with amphoteric surfactants, ensuring long-lasting foam stability and reduced formation damage in high-salinity conditions.
Patent Information
- Application Number
- CN202411258337.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Existing foam systems in oil and gas fields face challenges in high-salt environments due to poor stability and salt resistance, leading to foam destruction and formation damage, with conventional stabilizers causing viscosity issues and limited salt tolerance.
A carbonized polymer molecular cluster stabilized foam system is developed, prepared by reacting citric acid, taurine, and hexylamine, incorporating amino and sulfonic acid groups, forming a stable foam system with amphoteric surfactants and water, suitable for high-salinity conditions.
The system provides excellent salt resistance and stability, maintaining foam integrity for over 10 hours in high-mineralization environments, reducing formation damage and enhancing extraction efficiency in deep oil and gas fields.
Smart Images

Figure CN119242282A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field development, and in particular relates to a carbonized polymer molecular cluster stabilized foam system and a preparation method and application thereof. Background Art
[0002] At present, foam fluids are widely used in the development of oil and gas fields, and have a history of nearly 60 years at home and abroad. Foam has achieved certain results in many aspects of oil and gas field development, such as oil displacement, drainage and gas production of water-bearing gas wells, sand flushing and well washing, drilling, profile control, water plugging, acidification, cement cementing and fracturing. However, as most oil fields enter the middle and late stages of development, the drilling depth continues to increase, and the deep and high-mineralization formation water will significantly reduce the foaming volume of the foaming agent and significantly shorten the foam half-life. The sodium ions and calcium ions in the formation will neutralize the charge carried by the system, reduce the adsorption charge concentration of the foam liquid film, weaken the repulsion on both sides, and then lead to the destruction of the double electron layer structure, thinning the liquid film thickness, and accelerating the drainage speed, which greatly reduces the stability of the foam. In particular, anionic surfactants will precipitate when encountering inorganic salt ions. The salt ions in the formation react chemically with the foaming agent molecules to generate insoluble or insoluble salts, which destroy the molecular structure of the foaming agent, greatly deteriorate the activity or even inactivate it, and then affect the performance of the foam system.
[0003] There are two main methods to improve the stability of foam systems in high-salt environments. One is to screen and compound the foaming surfactants, and use the synergistic effect of different surfactants to improve the salt resistance of the foam system, or to graft and modify the existing surfactants, introduce salt-resistant characteristic groups and then compound them; the other is to improve the foam performance under high salt by adding foam stabilizers. Due to their macromolecular long chain or branched structure, polymers significantly increase the viscosity of the liquid phase in the foam system after dissolving in water, thereby reducing the drainage speed of the liquid film so that the liquid in the liquid film is not easy to lose, and at the same time reducing the permeability of the liquid film so that the gas in the foam is not easy to diffuse. They are often used as foam stabilizers. However, whether it is organic polymers or biomacromolecules, the addition of them increases the viscosity of the solution, but also leads to a decrease in the ability to generate foam, and it is not easy to inject into the formation due to excessive viscosity. In addition, polymers are easily degraded under high-salt reservoir conditions, the foam stabilization effect is greatly reduced, and the residual polymers may cause pollution to the formation. Another commonly used foam stabilizer is solid phase particles, which are used to assist the foam system in building a rigid liquid film structure to improve the stability of the foam and thus improve the salt resistance of the foam system. Patent CN201210223060 discloses a composite foam system with added nanoparticles for oil and gas fields and its preparation method. The system exhibits certain salt resistance at a mineralization of 25,000 mg / L, but the amount of SiO2 particles used is large, which limits its scope of application. In addition, the particle size of conventional nanoparticles is generally above 10 nm, and adsorption and retention on the surface of reservoir pore throats will damage the oil and gas layers to a certain extent. Summary of the invention
[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a carbonized polymer molecular cluster stabilized foam system and a preparation method and application thereof, and solve the technical problems of poor stability and salt resistance of the foam system in the prior art.
[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a carbonized polymer molecular cluster, which is prepared by dispersing citric acid, taurine and hexylamine in an alcohol solvent and subjecting them to a hydrothermal reaction.
[0006] In a second aspect, the present invention provides a carbonized polymer molecular cluster stabilized foam system, which comprises the following components, by mass: 0.03-0.1 parts of carbonized polymer molecular clusters, 0.5-0.8 parts of amphoteric surfactants, and 50-100 parts of water.
[0007] In a third aspect, the present invention provides a method for preparing a carbonized polymer molecular cluster stabilized foam system, comprising the following steps: S1, adding the carbonized polymer molecular clusters into water, and dispersing them evenly to obtain a carbonized polymer molecular cluster dispersion; S2, adding an amphoteric surfactant to the carbonized polymer molecular cluster dispersion, and dispersing them evenly to obtain a compound foam system solution; S3, stirring the compound foam system solution to foam, and obtaining a carbonized polymer molecular cluster stabilized foam system.
[0008] In a fourth aspect, the present invention provides an application of a carbonized polymer molecular cluster stabilized foam system as a foaming agent in oil and gas field development.
[0009] Compared with the prior art, the beneficial effects of the present invention include: The foam system provided by the present invention includes carbonized polymer molecular clusters, which have excellent salt resistance, and the raw material source is environmentally friendly and meets the requirements of green chemistry. The foam system not only improves the stability of the foam and reduces the risk of formation damage, but also effectively enhances the environmental friendliness of the system by optimizing the selection of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a schematic diagram of the structure of the carbonized polymer molecular cluster in the present invention.
[0011] Figure 2 This is a physical picture of the carbonized polymer molecular cluster-stabilized foam system changing over time in the present invention (200 mL solution, high-speed stirring at 4000 rpm for 3 min). DETAILED DESCRIPTION
[0012] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0013] The foam system in the prior art faces stability challenges in high-salt reservoir environments, especially for deep reservoir conditions with a salinity of more than 200,000 mg / L, and the traditional foam system has problems such as poor stability and salt resistance. In response to the above problems, the present invention is committed to developing a new foam system, which not only has excellent foaming ability and foam stability, but also has environmentally friendly raw material sources, in line with the principles of green chemistry, and is an ultra-stable carbonized polymer molecular cluster foam system suitable for high-salinity strata, which can solve the problems of insufficient salt resistance of the existing foam system in a high-salt environment, easy foam breakage, and residual damage to the strata. By applying the foam system of the present invention, it is expected to significantly improve the extraction efficiency of deep oil and gas fields and effectively protect the reservoir, thereby having a far-reaching impact on the sustainable development of oil and gas fields.
[0014] In a first aspect, the present invention provides a carbonized polymer molecular cluster, which is prepared by dispersing citric acid, taurine and hexylamine in an alcohol solvent and subjecting them to a hydrothermal reaction.
[0015] The present invention uses hexylamine as a raw material to react with citric acid and taurine to introduce amino groups and sulfonic acid groups; the functional group density of the carbonized polymer molecular cluster is 70-85%; the particle size distribution of the carbonized polymer molecular cluster is 3-5nm, which is nearly spherical, with a carbonized core inside and functional groups such as amino groups, sulfonic acid groups and hydroxyl groups distributed on the surface. The carbonized polymer molecular cluster provided in the present invention is small in size and has less damage to the reservoir pore throat structure than conventional granular plugging agents.
[0016] More preferably, the mass ratio of citric acid to taurine is (0.1-10):1; more preferably, the mass ratio is 1:1.
[0017] More preferably, the ratio of the mass of hexylamine to the total mass of citric acid and taurine is (2-6):1; more preferably 1:1.
[0018] More preferably, in the hydrothermal reaction, the reaction temperature is 140 to 180° C., and the reaction time is 8 to 12 hours.
[0019] More preferably, after the hydrothermal reaction is completed, a post-treatment is performed to obtain the carbonized polymer molecular clusters; the post-treatment is to remove the solvent by rotary evaporation at 40-60°C.
[0020] In a second aspect, the present invention provides a carbonized polymer molecular cluster stabilized foam system, which comprises the following components, by mass: 0.03-0.1 parts of carbonized polymer molecular clusters, 0.5-0.8 parts of amphoteric surfactants, and 50-100 parts of water.
[0021] Specifically, the amount of carbonized polymer molecular clusters can be selected from 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.1 parts or any value between 0.03 and 0.1 parts; the amount of amphoteric surfactant can be selected from 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts or any value between 0.5 and 0.8 parts.
[0022] Preferably, the following components are included, calculated by mass: 0.05 parts of carbonized polymer molecular clusters, 0.8 parts of amphoteric surfactants, and 100 parts of water.
[0023] Preferably, the amphoteric surfactant includes at least one of cocamidopropyl betaine, lauramidopropyl hydroxysulfonate, lauramidopropyl betaine, and cocamidopropyl hydroxysulfonate.
[0024] Preferably, the water is deionized or mineralized water.
[0025] More preferably, the mineralization degree of the mineralized water is 10000-250000 mg / L.
[0026] In a third aspect, the present invention provides a method for preparing a carbonized polymer molecular cluster stabilized foam system, comprising the following steps: S1, adding carbonized polymer molecular clusters into water and dispersing them evenly to obtain a carbonized polymer molecular cluster dispersion; S2, adding an amphoteric surfactant to the carbonized polymer molecular cluster dispersion to uniformly disperse the dispersion to obtain a composite foam system solution; S3, stirring and foaming the compound foam system solution to obtain a carbonized polymer molecular cluster-stabilized foam system.
[0027] Preferably, in step S1 and step S2, the dispersion method is ultrasonic dispersion at room temperature, the ultrasonic power is 100-200 W, and the ultrasonic time is 5-10 min.
[0028] Preferably, in step S3, the stirring and foaming is performed by a Waring Blender method, wherein the stirring speed is 4000-8000 rpm, the stirring time is 3 minutes, and the gas source includes one of air, nitrogen, carbon dioxide or natural gas.
[0029] In a fourth aspect, the present invention provides an application of a carbonized polymer molecular cluster stabilized foam system as a foaming agent in oil and gas field development.
[0030] Preferably, the oil and gas field is a high-mineralization oil reservoir, and the high-mineralization range is 10,000 to 250,000 mg / L.
[0031] The main mechanism of action and advantages of the present invention: (1) The present invention uses hexylamine as a raw material to react with citric acid and taurine to prepare a carbonized polymer molecular cluster, and the surface of the carbonized polymer molecular cluster has amino groups, sulfonic acid groups and hydroxyl groups; by controlling the ratio of hexylamine to citric acid and taurine, the ratio of hydrophilic and lipophilic groups of the carbonized polymer molecular cluster can be controlled, thereby achieving the regulation of the foam stabilization performance of the synthesized carbonized polymer molecular cluster. At the same time, the introduction of sulfonic acid groups improves the salt resistance of the carbonized polymer molecular cluster, and the unique structure of the molecular cluster can also improve the stability of the subsequent foam system.
[0032] (2) The present invention provides a solid, liquid and gas three-phase foam system, wherein the solid phase is a carbonized polymer molecular cluster having an amino group, a sulfonic acid group and a hydroxyl group, and the liquid phase comprises an amphoteric surfactant solution; and the carbonized polymer molecular cluster and the amphoteric surfactant and water form an ultra-stable foam system solution, which is stirred and foamed to form a three-phase foam system. The ultra-stable carbonized polymer molecular cluster foam system is suitable for high-mineralization formations and can overcome the problems of poor stability and salt resistance existing in traditional foam systems.
[0033] (3) The component materials of the foam system of the present invention have good performance and are added in a moderate proportion. The liquid separation half-life of the foam system prepared by the component materials can reach more than 10 hours, and it still has good performance in 210,000 mg / L brine. It can be used as a foaming agent in the increasingly demanding oil and gas field development process, such as oil recovery, water-containing gas well drainage, sand flushing, drilling, profile control, water plugging, acidizing, cementing and fracturing.
[0034] The present invention is further described in detail below through specific examples and comparative examples.
[0035] Example 1 (Carbonized polymer molecular clusters) A carbonized polymer molecular cluster, the preparation steps are as follows: (1) Weigh 2.5 g of citric acid, 2.5 g of taurine and 5 g of hexylamine to form a mixture, and add the mixture into 50 mL of ethanol; (2) After being evenly dispersed, pour into a 100 mL hydrothermal reactor and react at 140-180 °C for 10 hours; (3) After the reaction is completed, the solvent is removed by rotary evaporation at 50° C. to obtain the carbonized polymer molecular clusters.
[0036] like Figure 1 As shown, the carbonized polymer molecular cluster prepared by the present invention uses hexylamine as a raw material to react with citric acid and taurine, and the surface will carry amino groups, sulfonic acid groups and hydroxyl groups, and has a large specific surface area and surface structure, and has a strong adsorption effect on amphoteric surfactants. After compounding, it is easier to make the surfactant molecules in the adsorption layer more closely arranged through the interaction of hydrogen bonds or dipole moments, thereby increasing the viscosity and elasticity of the adsorption layer, increasing the stability of the adsorption film, and improving the foaming and foam stabilizing properties of the surfactant.
[0037] Example 2 (Carbonized polymer molecular cluster stabilized foam system) A carbonized polymer molecular cluster stabilized foam system, the preparation steps of which are as follows: S1: 0.1 g of carbonized polymer molecular clusters (prepared in Example 1) was added to 200 g of simulated saline with a salinity of 210,000 mg / L, and the beaker was placed in an ultrasonicator (power 150 W) for uniform dispersion to obtain a light yellow carbonized polymer molecular cluster dispersion; S2: adding 1.6 g of zwitterionic surfactant to the carbonized polymer molecular cluster dispersion obtained in S1, followed by ultrasonic dispersion to obtain a composite foam system solution; S3: 100 mL of the compound foam system solution prepared in S2 was poured into a high stirring cup and stirred at 8000 rpm for 3 minutes using a Waring Blender method to obtain a carbonized polymer molecular cluster stabilized foam system.
[0038] After stirring, quickly pour the foam into a 500 mL measuring cylinder and record the foam volume and liquid separation half-life.
[0039] Example 3 (Investigation of the influence of carbonized polymer molecular clusters on the performance of foam system) In order to verify the effect of different concentrations of carbonized polymer molecular clusters and surfactant compounding ratios on the foam system, a carbonized polymer molecular cluster stabilized foam system was prepared according to the mass ratio and method of Example 2 above, except that: in the carbonized polymer molecular cluster foam system, the amount of carbonized polymer molecular clusters relative to water was 0wt%, 0.03wt%, and 0.1wt%, respectively, which were recorded as the control group, test group A, and test group C, and Example 2 was recorded as test group B (the amount of carbonized polymer molecular clusters relative to water accounted for 0.05 wt%). The foaming volume and liquid separation half-life of the carbonized polymer molecular cluster stabilized foam system under different carbonized polymer molecular cluster dosages are shown in Table 1.
[0040] Table 1 Effect of carbonized polymer molecular clusters on foam system properties
[0041] As can be seen from Table 1, under a high mineralization environment of 210000 mg / L, the liquid precipitation half-life of the foam produced by a simple amphoteric surfactant (control group) is only 11 minutes, while the stability of the foam in test groups A to C is greatly improved after adding a trace amount of carbonized polymer molecular clusters. When the amount of carbonized polymer molecular clusters is 0.03%, the liquid precipitation half-life of the foam reaches 460 minutes; when the amount exceeds 0.05%, the liquid precipitation half-life increases slowly. Taking all factors into consideration, the preferred amount of the carbonized polymer molecular clusters of the present invention is 0.05%.
[0042] Example 4 (Investigation of the influence of mineralization on the stability of foam system by carbonized polymer molecular clusters) In order to verify the influence of different salinities on the foam system, the foam system was prepared according to the mass ratio and method described in Example 2, except that the simulated formation water salinity was 25000 mg / L and 250000 mg / L, respectively, as test group D and test group E. The foaming volume and liquid separation half-life of the carbonized polymer molecular cluster stabilized foam system under different salinities are shown in Table 2.
[0043] Table 2 Effect of mineralization on the carbonized polymer cluster-stabilized foam system
[0044] As shown in Table 2, with the increase of salinity, the foaming volume of the foam system is slightly reduced, but the liquid separation half-life is significantly increased. Under the condition of high salinity of 250000 mg / L, it also has a large foaming volume, a large liquid carrying capacity, and a liquid separation half-life of more than 10 hours, that is, the carbonized polymer molecular cluster stabilized foam system provided by the present invention has excellent salt resistance, which is enough to withstand a salinity of 210000 mg / L or even higher. At the same time, the higher the salinity, the better the stability of the foam system provided by the present invention, which is suitable for oil and gas field development under harsh conditions of high salinity.
[0045] Example 5 The only difference from Example 2 is that the rotation speed in the Waring Blender method is adjusted to 4000 rpm, 200 mL of the foam system solution is compounded, and the other steps and conditions are the same as in Example 2.
[0046] The obtained carbonized polymer molecular cluster stable foam was poured into a 500 mL measuring cylinder, and the actual picture of its change over time is as follows: Figure 2 As shown, it can be seen that its elution half-life reaches 12h.
[0047] Comparative Example 1 The only difference from Example 2 is that the amphoteric surfactant is replaced by anionic surfactant sodium α-olefin sulfonate (AOS), and the other steps and conditions are the same as those in Example 2.
[0048] The prepared foam system solution was poured into a 500 mL measuring cylinder. The foam volume was 325 mL, but the liquid separation half-life was only 20 min.
[0049] In summary, the present invention discloses a carbonized polymer molecular cluster, a stable foam system, a preparation method and an application thereof. The foam system comprises a gas phase, a liquid phase and a solid phase. The liquid phase is a zwitterionic surfactant solution, and the solid phase is a carbonized polymer molecular cluster. The carbonized polymer molecular cluster has functional groups such as amino groups, sulfonic acid groups and hydroxyl groups to achieve salt resistance of the foam system. The carbonized polymer molecular cluster and the zwitterionic surfactant can have a synergistic effect and adsorb on the gas-liquid interface of the foam, which significantly improves the structural strength of the foam liquid film, effectively slows down the flow of the liquid in the liquid film, reduces the drainage effect of the liquid film, thereby weakening the rupture of the liquid film, and achieving the ultra-stability of the foam in high-mineralization salt water. The composite foam system of the present invention has a 21×10 4 Under the condition of high mineralization degree of 1000 mg / L, the foaming volume can still reach more than 3 times of the original liquid, and the liquid separation half-life can reach more than 10 hours, which is enough to meet the requirements of the stability performance of the foam system during the development of oil and gas fields in the harsh environment of high mineralization degree.
[0050] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A carbonized polymer molecular cluster, characterized in that: The carbonized polymer molecular cluster is prepared by dispersing citric acid, taurine and hexylamine in an alcohol solvent and performing a hydrothermal reaction.
2. The carbonized polymer molecular cluster according to claim 1, characterized in that: The mass ratio of the citric acid to the taurine is (0.1-10):1; the mass ratio of the hexylamine to the total mass of the citric acid and the taurine is (2-6):
1.
3. The carbonized polymer molecular cluster according to claim 1, characterized in that: In the hydrothermal reaction, the reaction temperature is 140-180° C. and the reaction time is 8-12 hours.
4. A carbonized polymer molecular cluster stabilized foam system, characterized in that: The invention comprises the following components by weight: 0.03 to 0.1 parts of the carbonized polymer molecular cluster according to any one of claims 1 to 3, 0.5 to 0.8 parts of an amphoteric surfactant, and 50 to 100 parts of water.
5. The carbonized polymer molecular cluster stabilized foam system according to claim 4, characterized in that: The amphoteric surfactant includes at least one of cocamidopropyl betaine, lauramidopropyl hydroxysulfonyl betaine, lauramidopropyl betaine, and cocamidopropyl hydroxysulfonyl betaine.
6. The carbonized polymer molecular cluster stabilized foam system according to claim 4, characterized in that: The water is deionized water or mineralized water with a mineralization degree of 10,000 to 250,000 mg / L.
7. The method for preparing a carbonized polymer molecular cluster stabilized foam system according to claim 4, characterized in that: The following steps are involved: S1, adding carbonized polymer molecular clusters into water and dispersing them evenly to obtain a carbonized polymer molecular cluster dispersion; S2, adding an amphoteric surfactant to the carbonized polymer molecular cluster dispersion to uniformly disperse the dispersion to obtain a composite foam system solution; S3, stirring and foaming the compound foam system solution to obtain a carbonized polymer molecular cluster-stabilized foam system.
8. The method for preparing a carbonized polymer molecular cluster stabilized foam system according to claim 7, characterized in that: In step S1 and step S2, the dispersion method is room temperature ultrasonic dispersion, the ultrasonic power is 100-200W, and the ultrasonic time is 5-10min.
9. The method for preparing a carbonized polymer molecular cluster stabilized foam system according to claim 7, characterized in that: In step S3, the Waring Blender method is used for stirring and foaming, wherein the stirring speed is 4000-8000 rpm, the stirring time is 3 minutes, and the gas source includes one of air, nitrogen, carbon dioxide or natural gas.
10. Use of the carbonized polymer molecular cluster stabilized foam system as claimed in claim 4 as a foaming agent in oil and gas field development.
Citation Information
Patent Citations
Foam composition with improved foam durability
CN115813789A
Efficient moisturizing shower gel and preparation method thereof
CN116803370A
Carboxylic acid type carbon quantum dot foam system as well as preparation method and application thereof
CN116970380A
Cited By
Metal in-situ anchoring carbon nanocluster catalyst and preparation method and application thereof
CN121571207A